Populism and competitive authoritarianism in Turkey - Castaldo, Antonino (2020)
The main goal of this paper is to explain the rise of competitive authoritarianism in Erdoğan’s Turkey. The recent literature has mainly focused on the taxonomical debate about the type of regime established by Erdoğan, dealing only rarely with the factors explaining the Turkish autocratization. Building on Levitsky and Loxton’s framework, which underlines the catalyst role played by the election of populist leaders for the rise of competitive authoritarianism in Latin America, the analysis identifies the interactions among Erdoğan’s populism and threats and opportunities provided by both domestic and international environments as the major cause explaining Turkish autocratization.